2017
DOI: 10.1007/s00520-017-3919-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and coping strategies among women with incurable lung cancer: a qualitative study

Abstract: Women with incurable LC experienced substantial iterative psychological distress throughout the illness, regardless of length of illness at time of interview. They applied multiple forms of coping. The findings enrich the limited existing literature on this understudied population and provide direction for the future development of interventions to improve their psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 39 publications
7
56
0
1
Order By: Relevance
“…Participants mentioned that they faced reality with a positive attitude and constantly relieved themselves of their negative emotions so that their life could move on. Similar coping strategies were also reported in a previous study of patients with lung cancer, which stated that positive thoughts could reduce stress from current situations (Liao, Liao, Sun, Ko, & Yu, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…Participants mentioned that they faced reality with a positive attitude and constantly relieved themselves of their negative emotions so that their life could move on. Similar coping strategies were also reported in a previous study of patients with lung cancer, which stated that positive thoughts could reduce stress from current situations (Liao, Liao, Sun, Ko, & Yu, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…Reduced physical functioning due to disabling symptoms, and reduced wellbeing and functioning in psychological, work and social spheres have been reported in those living with other illnesses [ 23 ]. Shock at receiving a diagnosis of an incurable illness and feeling distressed about the progressive nature of it is recognised in the narratives of those living with incurable cancer [ 24 ]. Participants’ sense of isolation and loneliness is also reflected in the accounts of those living with rare, incurable or painful illness [ 25 – 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants’ sense of isolation and loneliness is also reflected in the accounts of those living with rare, incurable or painful illness [ 25 – 27 ]. Finally, coping responses such as denial, acceptance, positivity and slowing down the pace of life were reported by individuals who, like many of those living with PSC, had multiple chronic conditions or were living with incurable cancer [ 24 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Although some qualitative research has identified coping mechanisms for managing depressive symptoms in cancer patients parallel to those identified here, such as coping through faith, social support, thinking positive, and using avoidance based strategies, this limited research did not report the ethnic identity of cancer survivors. 39 More research on ethnic minorities, comparing AI/AN populations with other women is needed. This qualitative study is not generalizable beyond its setting.…”
Section: Study Limitations and Future Researchmentioning
confidence: 99%